The double-bind: looked after children, care leavers, and criminal justice - Carr, Nicola; McAlister, S. (Palgrave Macmillan, 2016)
Research attention has focused on the reasons that lead young people from care to come into contact with the justice system at higher rates than young people within the general population. Findings from this literature can be distilled into three main themes. Firstly, many young people in care have experienced a range of adversities that place them at higher risk of offending. Secondly, the care experience may in itself be ‘criminogenic’. Thirdly, the transition to adulthood for young people leaving care is often compressed and accelerated, placing them at increased vulnerability to a range of negative outcomes. This chapter reviews this literature and argues that the findings from research on desistance may provide a useful framework for considering future areas of research and implications for practice.